2022
DOI: 10.5961/higheredusci.907512
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinin Çocuk İstismarı ve İhmalinin Belirti ve Risklerini Tanılamaya İlişkin Bilgi Düzeyleri

Abstract: Amaç: Bu çalışma, hemşirelik öğrencilerinin çocuk istismar ve ihmalinin belirti ve risklerini tanılamaya ilişkin bilgi düzeylerini belirlemek amacıyla yapılmıştır. Gereç ve Yöntem: Çalışma tanımlayıcı tipte olup, Ankara’da bulunan bir devlet üniversitesinin Hemşirelik Bölümü’nde okuyan, gönüllü, 2., 3. ve 4. sınıf hemşirelik öğrencileri (N=270) ile gerçekleştirilmiştir. Verilerin toplanmasında, öğrencilerin tanıtıcı özelliklerine ilişkin anket formu, öğrencilerin çocuk istismar ve ihmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…play a role in awareness and knowledge of child abuse and neglect (Erkut et al, 2021). Several studies have reported that the sociodemographic and cultural characteristics of nursing students significantly affect their knowledge and awareness of child abuse and neglect (Gudek Seferoglu et al, 2019; Özbey et al, 2018; Özçevik et al, 2018; Topçu et al, 2022). An additional study revealed that while the age of the participants was not a factor, there was a significant difference between the awareness levels of students on child neglect and abuse with the variables of gender, class, information about child neglect and abuse, child neglect and abuse case or suspicion (Tek & Karakaş, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…play a role in awareness and knowledge of child abuse and neglect (Erkut et al, 2021). Several studies have reported that the sociodemographic and cultural characteristics of nursing students significantly affect their knowledge and awareness of child abuse and neglect (Gudek Seferoglu et al, 2019; Özbey et al, 2018; Özçevik et al, 2018; Topçu et al, 2022). An additional study revealed that while the age of the participants was not a factor, there was a significant difference between the awareness levels of students on child neglect and abuse with the variables of gender, class, information about child neglect and abuse, child neglect and abuse case or suspicion (Tek & Karakaş, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of adequate training on CAN and insufficient studies on this subject cause a lack of knowledge, and cases may be ignored. For example, in Turkey, only a few universities offer elective courses on CAN in the nursing curriculum (Topçu et al, 2022). In parallel, only a few studies have shown that CAN knowledge and awareness levels are good regarding including this topic in the paediatric nursing curriculum (Özçevik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses should communicate with the child and their family, try to understand the signs and symptoms of abuse and neglect and report them as forensic cases (Chen et al, 2022). In order to fulfil these roles and responsibilities appropriately, they should be trained in CAN (Topçu et al, 2022). Lack of adequate training on CAN and insufficient studies on this subject cause a lack of knowledge, and cases may be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Given that all children are at risk of child abuse, it is important and necessary for undergraduate health students to have knowledge about diagnosing the symptoms and risks of child maltreatment, especially as future health professionals. Although the studies on the level of knowledge about child abuse among students studying in undergraduate programs related to health sciences are quite limited, it has been found that students' knowledge about this topic is insufficient, their level of identification of symptoms and risks is not at the desired level, and they need information about this topic 8 , 9 . In addition, according to the results of the research, public students know very less about sexual infection disease and male adolescents are less interested in health services 10 .…”
Section: Introductionmentioning
confidence: 99%